(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
This paper develops primarily an analytical solution for sound, electromagnetic or any other wave propagation described by the Helmholtz equation in the case of N circular obstacles. Then, it proposes a fast iterative numerical method, using Toeplitz block structure, for computing the solution of a complex, dense and large linear system. Finally, it shows the efficiency of this numerical strategy via a numerical study of the convergence rate with respect to different geometrical parameters of the problem.